Respostas
respondido por:
3
X² - 10x + 25 = 0
Delta = b² - 4ac
Delta = (-10)² - 4(1)(25)
Delta = 100 - 100
Delta = zero
X = (-b +- raiz delta) / 2a
X = (10 +- 0) / 2
x' = (10 + 0) / 2 = 10/2 = 5
x" = (10 - 0) / 2 = 10/2 = 5
Delta = b² - 4ac
Delta = (-10)² - 4(1)(25)
Delta = 100 - 100
Delta = zero
X = (-b +- raiz delta) / 2a
X = (10 +- 0) / 2
x' = (10 + 0) / 2 = 10/2 = 5
x" = (10 - 0) / 2 = 10/2 = 5
respondido por:
1
a= 1
b= 10
c=25
Δ= b² - 4·a·c
Δ= 10² - 4·1·25
Δ= 100 - 100
Δ= 0
x= -b +- √Δ /2.a
x= -10 +- 0/2·1
x1= -10 - 0/2 = -10/2= -5
x2= -10 + 0/2 = -10/2= -5
x1=x2= -5
b= 10
c=25
Δ= b² - 4·a·c
Δ= 10² - 4·1·25
Δ= 100 - 100
Δ= 0
x= -b +- √Δ /2.a
x= -10 +- 0/2·1
x1= -10 - 0/2 = -10/2= -5
x2= -10 + 0/2 = -10/2= -5
x1=x2= -5
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás